2011
DOI: 10.1167/11.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential attentional modulation of cortical responses to S-cone and luminance stimuli

Abstract: Neural signals driven by short-wave-sensitive (S) cones are, to a large degree, anatomically and functionally separate from the achromatic luminance pathway until at least one synapse into V1. Attentional mechanisms that act at an anatomically early stage in V1 may, therefore, affect S-cone and luminance signals differently. Here, we used a steady-state visually evoked potential (SSVEP) paradigm combined with electrical source imaging to study the effects of contrast and attention on neural responses to both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 77 publications
(106 reference statements)
0
27
0
Order By: Relevance
“…The fact that the relative activation across area depends on both task, and on the specific cortical area strengthens our claim that we have identified independent sources. While the technique of source imaging combined with high-density EEG and individual head models and retinotopic ROIs is relatively new (Appelbaum, Wade, Vildavski, Pettet, Norcia 2006), several recent studies have shown that it can be used to measure robust effects of both attention and center-surround interactions (Lauritzen et al, 2010; Xiao and Wade, 2010; Wang and Wade, 2011). In addition, recent work from our group has shown that crosstalk between visual area clusters is not a significant source of error in these types of measurement (Lauritzen et al, 2010; Cottereau et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the relative activation across area depends on both task, and on the specific cortical area strengthens our claim that we have identified independent sources. While the technique of source imaging combined with high-density EEG and individual head models and retinotopic ROIs is relatively new (Appelbaum, Wade, Vildavski, Pettet, Norcia 2006), several recent studies have shown that it can be used to measure robust effects of both attention and center-surround interactions (Lauritzen et al, 2010; Xiao and Wade, 2010; Wang and Wade, 2011). In addition, recent work from our group has shown that crosstalk between visual area clusters is not a significant source of error in these types of measurement (Lauritzen et al, 2010; Cottereau et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…46-11.57, p's ≤ 0.028;(Di Russo, Spinelli, & Morrone, 2001;Sirawaj Itthipuripat, Garcia, Rungratsameetaweemana, Sprague, & Serences, 2014;Kim, Grabowecky, Paller, Muthu, & Suzuki, 2007;Norcia, Appelbaum, Ales, Cottereau, & Rossion, 2015;W. & J., 1972;Wang & Wade, 2011)). This indicates that increasing target contrast successfully increased the amount of sensory evidence represented in visual cortex.…”
Section: Speed Goals Do Not Modulate Early Sensory Responsesmentioning
confidence: 98%
“…SSVEP amplitudes were estimated from data averaged over trials within each contrast and SAT condition at central occipital electrode Oz using a wavelet transform with a Gaussian frequency domain kernel with 2 Hz FWHM (0.8493 Hz SD)(Di Russo et al, 2001;Sirawaj Itthipuripat et al, 2014;Kim et al, 2007;Norcia et al, 2015;W. & J., 1972;Wang & Wade, 2011). The absolute values of these complex coefficients were then taken to obtain SSVEP amplitude measures for each contrast and SAT condition.…”
Section: Eeg Analysismentioning
confidence: 99%
“…are standard and have been described in detail previously . Retinotopic field mapping produced ROI-defined visual cortical areas V1, V2v, V2d, V3v, V3d, V3a, and V4 in each hemisphere (Tootell and Hadjikhani, 2001;Wang and Wade, 2011). ROIs corresponding to the human middle temporal area (hMTϩ) were identified using low-contrast motion stimuli similar to those described by Huk et al (2002).…”
Section: Visual Area Definitionmentioning
confidence: 99%
“…Magnocellular neurons, which show transient onset and offset response profile, are a likely substrate for generating the second-harmonic response, although they may not generate a robust first harmonic to an on-off stimulus (Kulikowski et al, 1997). It has also been reported that the magnocellular pathway shows a robust modulation due to attention (Di Russo and Spinelli, 1999;Wang and Wade, 2011).…”
Section: Roi-based Analysis Of the Ssvepmentioning
confidence: 99%